2022
DOI: 10.1007/s11846-022-00550-8
|View full text |Cite
|
Sign up to set email alerts
|

Economic policy uncertainty and corporate donation: evidence from private firms in Korea

Abstract: This study examines the association between economic policy uncertainty (EPU) and private firms’ corporate donations. Based on resource constraints and the conservation of resources (COR) theory, we argue that private firms are constantly facing resource constraints and their resource conservation motive becomes apparent when EPU is heightened. Therefore, we expect that corporate donations are negatively related to EPU. Using audited corporate donations from 48,903 private firms in Korea during 2002–2019, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
(144 reference statements)
0
0
0
Order By: Relevance
“…Meanwhile, extant literature has shown that Korean government and ruling party' policy significantly affect firms' operations (e.g., Chiu et al, 2005;Ducret & Isakov, 2020;Kim, 2021;Song et al, 2014). For example, Chun et al (2023) document that Korean private firms are likely to increase the corporate donation when the incumbent government is progressive party rather than conservative party. This heightened pressure for corporate donation leads to an unwanted resource allocation, which would generate the incentive for accounting manipulation and delay the recognition of bad news.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, extant literature has shown that Korean government and ruling party' policy significantly affect firms' operations (e.g., Chiu et al, 2005;Ducret & Isakov, 2020;Kim, 2021;Song et al, 2014). For example, Chun et al (2023) document that Korean private firms are likely to increase the corporate donation when the incumbent government is progressive party rather than conservative party. This heightened pressure for corporate donation leads to an unwanted resource allocation, which would generate the incentive for accounting manipulation and delay the recognition of bad news.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…For example, Chun et al. (2023) document that Korean private firms are likely to increase the corporate donation when the incumbent government is progressive party rather than conservative party. This heightened pressure for corporate donation leads to an unwanted resource allocation, which would generate the incentive for accounting manipulation and delay the recognition of bad news.…”
Section: Literature Review Theoretical Framework and Hypothesis Devel...mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhao et al also found that the effect of EPU on various dimensions of CSR is still significantly negative [16]. Firms tend to reduce their charitable giving to conserve resources as a precautionary move in an environment with high EPU [17,48]. Su et al observed the negative effect between EPU and CSR in food enterprises, which are a part of a sensitive industry [49].…”
mentioning
confidence: 99%